Isolation and establishment of trans-cinnamic acid as a reference standard from Radix Scrophularia buergeriana Miq - Ngan Nguyen Kim Luu,, Ngan My Tran,, Phuong Thu Tran,, Duong Hoang Trinh (Journal of Applied Pharmaceutical Science, 2024)
Scrophularia buergeriana Miq., belonging to the family Scophulariaceae, is a potential medicinal herb that has been used in traditional oriental medicine since ancient times. However, studies of S. buergeriana are still at a relatively early stage. Above all, there is still no established reference standard to control the quality of medicinal herbs and their products from S. buergeriana in Vietnam. Therefore, we present the isolation of trans-cinnamic acid from the root of S. buergeriana which was subsequently established as a chemical reference standard in this study. The isolation was conducted by recrystallization and CC on silica gel using different eluents. The purity and quality of the isolated compound were evaluated by spectroscopic methods and high-performance liquid chromatography (HPLC). Furthermore, the compound was evaluated for homogeneity and assigned value to establish reference standards according to General requirements for the competence of reference material producer’s guideline (TCVN ISO 17034:2017), Appendix 3 of World Health Organization (WHO technical report No. 943:2006) and Statistical methods for use in proficiency testing by interlaboratory comparison (ISO 13528:2015). The research successfully demonstrated the isolation and establishment of trans-cinnamic acid as a chemical reference standard for S. buergeriana which was herein reported for the first time.
Keywords: Scophulariaceae, Scrophularia buergeriana Miq., reference standard, isolation, establishment